Ethnobotanical study and nutrient content of local vegetables consumed in Central Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2016)
Chotimah HENC, Kresnatita S, Miranda Y. 2013. Ethnobotanical study and nutrient content of local vegetables consumed in Central Kalimantan, Indonesia. Biodiversitas 14: 106-111. People in Central Kalimantan consume vegetables collected from the wild or traditionally cultivated. Documentation effort of them is very important because the diversity of local vegetables is threatened with extinction due to the conversion of peat land and forest fires. This study aimed to determine the diversity of local vegetables in Central Kalimantan, its use as a vegetable and nutrient content of some vegetables. The method used was the exploration and interviews. Exploration was carried out in three districts, namely Palangkaraya, Pulang Pisau, and Seruyan. Sampling of plants was done randomly and selectively. Data analysis was performed descriptively. The results showed that we recorded 42 plant species belonging to 30 families. There were many vegetables processing: stir-fry, make into clear soup, a light coconut milk soup, acidic soup, or just consumed as fresh vegetables. Based on the nutritional value, Helminthostachys zeylanica (L.) Hook had a potential to be developed as vegetables or medicinal plant. It had the highest protein, carbohydrate and minerals, namely P, Fe, Na and K among the vegetables analyzed.